Situation Analysis and Needs Assessment Report for Tra Hat Village, Bac Lieu Province, Vietnam - Minh ND; Truc NT; Phong ND; Duong LM; Ngoc Chi TT; Binh NT; Ferrer, Alice J.; Yen, B.T.; Sebastian, Leocadio S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Bac Lieu Province in Vietnam is mainly agricultural. Rice is the dominant staple food and the main crop in the province. Farmers have changed the farming system from paddy monoculture to diversified agricultural products (cash crops and livestock). Livestock production is in small scale. The province has three ecological zones: rice/fruit and vegetable production in the eastern districts, a mixed rice and rice/shrimp/aquaculture environment in the central districts and an area of saline/acid soil for a wide variety of sea-based product in the western districts. Salinization and shifting land use from cultivation to aquaculture have caused soil degradation in Bac Lieu. Meanwhile, Tra Hat village is in Vinh Loi District in Bac Lieu Province. It is about 25 km distance from Bac Lieu City. Nearly 80% of the total area of 400 ha of the village are paddy fields (316 ha). Livelihood in the village include rice production, livestock, fishpond and garden production. The problems in rice production include the degradation of the traditional rice seed, flooding, lack of freshwater, application of more farm chemicals, and difficult access to market information; for fruits and vegetables, the main problem is the poor market demand; for livestock, the main problems are diseases and lack of market; in fisheries, the main problem is the low catch; and for aquaculture, the main problems are the poor quality of water and the lack of market. Households also earn money from off farm activities and thus can buy other food (meat, egg) at the commune market for daily consumption. Many households in the village are food sufficient. The local production systems are well adapted to the natural seasonal fluctuation in rainfall and flooding regime, but occasional extreme flooding events cause crop damage and food shortage situation, the most recent was in 2011. The main concern is the maintenance of food sufficiency and security, and raising household income. The main challenges are increasing climate shocks, salt-water intrusion, and population growth. Households acknowledged their need to receive support from the government and other organizations to develop their production systems for sustainable and stable income and better living conditions with reduced risks of environmental pollution, natural disasters, and climate variability.